D2 림프절 절제를 동반한 전복강경하 유문보존위절제술 - 김진조(Jin Jo Kim); 송교영(Kyo Young Song); 진형민(Hyung Min Chin); 김욱(Wook Kim); 전해명(Hae Myoung Jeon); 박조현(Cho Hyun Park); 박승만(Seung Man Park); 안창준(Chang Jun Ahn); 임근우(Keun Woo Lim); 박우배(Woo Bae Park); 김승남(Seung Nam Kim) (Annals of surgical treatment and research, 2006)
To improve postoperative quality of life, and to avoid postgastrectomy syndrome, pylorus-preserving gastrectomy (PPG) is considered as a good option in the middle third early gastric cancer. Convetional PPG has limitation in number 5 lymph node dissection because of preservation of blood supply and nerve innervation to the pylorus. To expand the indication of PPG, limitation on lymph node dissection must be overcomed. In case of laparoscopic PPG, there have been few reports in the literature. Herein we report a case of totally laparoscopic PPG with D2 lymph node dissection with review of literature. (J Korean Surg Soc 2006;71:65-68) KCI Citation Count: 1